Strategi Nafkah dan Pemanfaatan Relasi-Relasi Sosial Rumahtangga Petani Kelapa Sawit - Tinur Fitri Ayu Harahap; Arya Hadi Dharmawan (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2018)
This study aims to identify the structure and strategy of the household livelihoods, identify the utilization of livelihood capital that influences household livelihood strategies of oil palm farmers and identifies the utilization of social relationships of oil palm farmers' households. There is a difference in the livelihood structure of households of oil palm self-reliant with plasma palm oil farmers. This research is done by quantitative method supported by qualitative data. The result of this research is explaining that the average of households' livelihood structure of palm oil farmers is from non-farm sector, whereas in households of plasma oil palm farmers is dominated by on farm sector supported by non-farm sector. The utilization of subsistence capital by two types of oil palm farmers is also different. Both types of farmers have diverse social relationships in support of farm household income.Keywords: livelihood assets, livelihood strategies, oil palm farmer household, social relations———————– ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi struktur dan strategi nafkah rumah, mengidentifikasi pemanfaatan modal nafkah yang mempengaruhi strategi nafkah rumahtangga petani kelapa sawit serta mengidentifikasi pemanfaatan relasi-relasi sosial rumahtangga petani kelapa sawit. Terdapat perbedaan struktur nafkah rumahtangga petani kelapa sawit swadaya dengan petani kelapa sawit plasma. Penelitian ini dilakukan dengan metode kuantitatif yang didukung oleh data kualitatif. Hasil penelitian ini memaparkan bahwa secara rata-rata struktur nafkah rumahtangga petani kelapa sawit swadaya berasal dari sektor non farm, sedangkan pada rumahtangga petani kelapa sawit plasma didominasi oleh sektor on farm yang didukung oleh sektor non farm. Pemanfaatan modal nafkah oleh dua jenis petani kelapa sawit juga berbeda. Kedua jenis petani ini memiliki relasi sosial yang beragam dalam mendukung pendapatan rumahtangga petani.Kata Kunci: modal nafkah, petani kelapa sawit, relasi sosial, strategi nafkah